Relationship of morphological changes of blood cells with endothelial function, renal function and lipidemic profile in patients with type 2 diabetes mellitus with suboptimal glycemic control and hypertension. - Pertseva, N. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Many questions about the relationship between endothelial dysfunction and morphological substrate of hemostasis damage that occur during the progress of type 2 diabetes mellitus and arterial hypertension require clarification and further advance. Objective. The aim of this study is to determine the relationships between endothelial dysfunction, the degree of renal function damage, lipidemic profile and morphological changes of vascular-platelet hemostasis in patients with type 2 diabetes mellitus with suboptimal glycemic control and hypertension. Methods. In 87 patients with insufficient glycemic compensation using clinical, laboratory, morphological methods and correlational analysis were identified association between endothelial dysfunction, degree of renal function damage, lipidemic profile and morphological changes of vascular-platelet hemostasis. Results. Against the background of insufficient glycemic compensation glycated hemoglobin concentration tightly correlated with the share of activated platelets (r=+0.77; p<0.05), with the level of aggregated forms (r=+0.82; p<0.05) and the concentration of small blood platelet aggregates (r=+0.76; p<0.05), established a positive relationship with the share degranulated platelets (r=+0.60; p<0.05). Signs of atherogenic dyslipidemia triad that this contingent of patients indicated significant deviation from that of the control group not only had a correlation with the share of activated platelets and content of alpha and delta granules, but also formed a new moderate strength correlations with other observable parameters of platelet morphology. In particular, amid insufficient glycemic compensation formed reliable values of the coefficients of linear correlation in pairs: total cholesterol and activated platelets (r=-0.54), low density lipoprotein cholesterol and activated platelets (r=-0.51), low density lipoprotein cholesterol and aggregated forms (r=+0.59), low density lipoprotein cholesterol and degranulated platelets (r=+0.48). Also triglycerides level in these patients established statistically significant correlation with all studied parameters of intravascular platelet activation. Conclusion. It has been established that in the insufficient glycemic control by a significant strengthening relationships between indicators of endothelial dysfunction and damaged platelet hemostasis formed significant correlations of ultrastructural characteristics of platelets with clinical and laboratory signs of nephropathy and dyslipidemic changes.